Chondrogenesis of adipose-derived stem cells with chondrocytes in low serum towards clinical application - Adila A. Hamid,; Satish Vaarman Jeyabalan,; Aleza Omar,; Nik Zattil Hanan Mohd Yasin,; Wong, Tzeng Lin; Liau, Ling Ling; Nur Azurah Abdul Ghani,; Aneeza Khairiyah Wan Hamizan,; Chia, Kien Hui (Penerbit Universiti Kebangsaan Malaysia, 2018)
Currently, fetal bovine serum (FBS) have been widely use in culture media to promote human cell proliferation. However, the usage of FBS for cell therapy in clinical application was associated with the risk of viral and prion transmission as well as immune rejection. To provide an option for this risk, this study was conducted to determine the effect of adipose derived stem cells (ADSCs) co-culture with chondrocyte in promoting cell proliferation and chondrogenesis toward FBS free condition. ADSCs co-cultured with chondrocyte at the ratio of 1:1, 2:1 and 1:2 were tested. Cell morphology changes, cell proliferation and gene expression level of stemness (Oct4, FGF-4, Nanog) and chondrogenic (Collagen Type II, ACP) were assessed. The results showed ADSCs in all co-culture groups changed morphology from fibroblastic spindle to polygonal shape which resembled chondrocytes. The morphological changes were accompanied with increased expression of chondrogenic genes; denoted chondrogenesis process. While maintaining expression of stemness genes indicated continuation of cell proliferation. From the three co-culture groups tested; ADSCs and chondrocytes (1:1 ratio) have been shown to exert better effects in promoting cell proliferation and chondrogenesis. In conclusion, ADSCs could replace FBS to grow sufficient number of chondrogenic cells to repair cartilage injury in the near future. Further in vivo study should be performed to test the effectiveness of this co-culture technique in cartilage injury repair.